2005
DOI: 10.1097/01.ju.0000150522.82760.00
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Nomogram for Predicting Positive Repeat Biopsy for Prostate Cancer

Abstract: Our corrected nomogram for predicting positive repeat biopsy performed well when applied to a sample of men at the Brooklyn Veterans Administration Medical Center. This nomogram can provide important additional information to aid the urologist and patient with a negative biopsy in evaluating clinical options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 16 publications
0
43
1
3
Order By: Relevance
“…The high specificity of these markers may aid in refining current algorithms for risk assessment in prostate cancer (25)(26)(27). For example, cancer prevalence in the population of patients having PSA Ͻ4 g/L when both cohorts were combined (n ϭ 70) was 44%.…”
Section: Discussionmentioning
confidence: 99%
“…The high specificity of these markers may aid in refining current algorithms for risk assessment in prostate cancer (25)(26)(27). For example, cancer prevalence in the population of patients having PSA Ͻ4 g/L when both cohorts were combined (n ϭ 70) was 44%.…”
Section: Discussionmentioning
confidence: 99%
“…It is been suggested that a nomogram validated by Yanke et al be used when deciding on a repeat biopsy (18). In this nomogram, parameters such as age, family history, PSA, PSA velocity, rectal exam findings, time elapsed following the initial biopsy procedure, the cumulative negative foci number, the presence of a diagnosis of HGPIN/ASAP in previous biopsies are used as risk factors (18). Nowadays, however, there is consensus about the performance of a repeat biopsy in cases where ASAP is detected.…”
Section: Discussionmentioning
confidence: 99%
“…Tres trabajos estudian pacientes con biopsias previas negativas [7][8][9] . El resto analizan la probabilidad de una biopsia prostática positiva para tumor.…”
Section: Discussionunclassified